World Bank Lending and Financial Sector Development - Cull, Robert; Effron, Laurie (World Bank, 2012)
A new database of World Bank loans to support financial sector development is used to investigate whether countries that received such loans experienced more rapid growth on standard indicators of financial development than countries that did not. Self-selection is accounted for with treatment-effects regressions. The results indicate that borrowing countries had significantly more rapid growth in M2/GDP than nonborrowers and swifter reductions in interest rate spreads and cash holdings (as a share of M2). Borrowers also had higher private credit growth rates than nonborrowers in some treatment-effects regressions but not in standard panel regressions with fixed country effects. On the whole, the results indicate some significant advantages in financial development for borrowers over nonborrowers.